Hydrodynamic Analysis of KVLCC2 Ship Sailing near Inclined Banks. (13th February 2021) - Luo, Weilin; Yang, Bing; Sun, Yafeng
Abstract : The hydrodynamic forces of KVLCC2 ship sailing near inclined banks are calculated by using CFD based on RANS equation. Corresponding CFD uncertainty analysis is conducted according to the procedure recommended by ITTC. An unstructured grid, tetrahedral grid, is employed for discretization. To control the number of grids, global element scale factor is selected as the same as refinement ratio. In numerical simulation, straightforward and oblique navigation conditions are investigated. The variation of transverse force and yaw moment with the ship-shore distance, bank angle, water depth, and drift angle are analyzed. Both hull model and hull-propeller-rudder model are considered in numerical simulation. The simulation results show the hydrodynamic characteristics of ship sailing near inclined banks.